PELATIHAN DAN PENDAMPINGAN UMKM TERHADAP PAJAK PERTAMBAHAN NILAI (PPN) PADA CV. X KOTA PADANG - Riyanti, Friska Felicia; Silmi, Silmi (Ensiklopedia of Journal, 2024)
This study examines tax mentoring practices in SMEs, focusing on CV. Multi Sarana, an automotive workshop located in Padang, West Sumatra. The research employs a fieldwork approach to investigate tax reporting, including direct mentoring by students, tax document verification, and the identification and reporting of Value Added Tax (VAT). Despite being non-PKP, CV. Multi Sarana shows that they have not fully grasped the process of reporting VAT Periodic Tax Returns (SPT Masa PPN), indicating a need for training and mentoring to enhance understanding and effective implementation. The activities took place from March to June 2024 with the aim of improving tax awareness and compliance. The results underscore the importance of hands-on fieldwork in supporting SMEs in effectively managing their tax obligations.